Respuesta :
Answer:
A) 1.5
B) x^2-23x+42 = (x-2)(x-21)
C) x=2, x=21
Step-by-step explanation:
a) 15 -2x / 3 = 4
15-2x = 12 (Times by three on both sides)
-2x = -3
x = -3/-2 = 3/2 = 1.5
b) x^2-23x+42
x^2-23x+42 = (x-2)(x-21)
c) x^2 -23x +42 = 0
x=2, x=21
(x-2) = 0 ⇒ x = 2
(x-21) = 0 ⇒ x = 21
Answer:
a) x = 1.5
b) (x-21)(x-2)
c) x = 2, 21
Step-by-step explanation:
a) Solve for x
(15 -2x)/3 = 4
15-2x = 12
2x = 3
x = 1.5
b) Factorize
x²-23x +42
x²-21x-2x+42
x(x-21)-2(x-21)
(x-21)(x-2)
c) Solve the two possible answers below
x^2 -23x +42 = 0
(x-21)(x-2) = 0
x = 2, 21